Resistensi Pedagang Kaki Lima dalam Ruang Publik di Tengah Situasi Pandemi Covid-19 - Nourma Ulva Kumala Devi (Universitas Islam Malang, 2021)
The Covid-19 pandemic situation, which is still happening today, is causing concern among people from various circles, especially for street vendors (PKL) at the Probolinggo Gotong Royong traditional market. Government regulations to suppress the spread of the virus by requiring people to carry out social distancing have an impact on the paralysis of economic activities for traders. In addition, various media continue to broadcast and report on street vendors who cannot follow government directives to stay at home, because of the demands of work and the pressure of daily needs. This study aims to find out how the efforts of traders to respond to government policies to stay afloat in locations that are considered strategic for trading in the midst of the Covid-19 pandemic situation. Then this study also aims to determine the impact felt by traders when social distancing is enforced. This research method is descriptive qualitative research with a case study approach through data analysis of pattern matching and theoretical propositions. This study uses Jurgen Habermas's scheme of thinking about the